Health service utilization patterns by preschool children with autism spectrum disorder compared to those with global developmental delay at a tertiary centre in South Africa - Oringe, Florence Nafula (Department of Paediatrics and Child Health, 2021)
Background Children with autism spectrum disorder (ASD) and those with global developmental delays (GDD) have complex health care needs that span long periods. Affected families in low resourced countries face substantial barriers in accessing care. Challenging behaviours in children with ASDs further complicates their service encounters and may result in forgone care, resulting in poor outcomes. Aim The aim of the study was to compare health service use (HSU) by preschool children with ASD and GDD attending developmental services at a tertiary hospital, and to explore the major factors impacting patterns of access. Methods A retrospective cohort study was done, where 240 children with ASD and GDD (Non -ASD) were enrolled at a ratio of 1:1. HSU was determined by a retrospective review of their medical records, in the preceding 1 year. A structured questionnaire administered sought information on socio-demographics, child characteristics, perspectives, family distress level, experiences, and level of service satisfaction. Descriptive statistics and logistic regression analysis were used to evaluate primary study questions. Ethical approval was obtained by the University of Cape Town Human Research Ethics Committee (HREC: 397/2019). Families gave informed consent prior to enrolment. Results A total of 240 children were enrolled,116 had ASD and 124 had GDD. Their median age was 5.2 years, and male: female ratio was 2:1. Higher co-occurring syndromic diagnoses were documented in GDD vs ASD at (46/124, 37.1% versus 14/116, 9.5%); (p<0.01) as well as higher comorbid diagnoses in GDD vs ASD at (51/124, 41.0% vs 14/116, 12.1%); (p=0.0001). A higher mean total health care visits was reported in those with GDD vs ASD (13.3 versus 11.5 (p=0.02), primarily due to higher specialist visits at 4.0 (2.0-5.5) vs 2.0 (2.0-3.0) (p<0.0001). Attendance for other services were similar in both groups, including therapy 6.0 (2.0-10.0), auxiliary services xiii 0 (0-1.0), emergency visits 1.0 (1.0-2.0), and primary care visits 0 (0-1.0). Respiratory infections (91/240;37.9%) and unspecified fever (57/240; 23.8%) were the leading reasons for emergency visits in this cohort. Hospitalization was higher among children with GDD (38/124, 31%) than ASD (16/116, 14%), p=0.02. Factors associated with higher HSU included primary diagnosis of GDD (p=0.02), female (vs male, average 1.59 more annual visits, p=0.04), being younger at first diagnosis (<2 vs ≥ 2 years, 1.72 more annual visits, p= 0.02), and having a concurrent syndromic diagnosis (vs none, 2.19 more annual visits, p=0.01). On logistic regression, controlling for these confounders, parental employment emerged as the strongest residual predictive factor for increased HSU (β 1.49, 95% CI -0.02 to 3.00, p=0.05). Conclusion: Children with GDD had greater service use than those with ASD, primarily due to higher specialist visits for their higher syndromic and comorbid diagnoses. Core therapy services were underutilized despite being key interventions in both groups. Parental employment, an enabling factor, predicted greater service use. This calls for systemic reduction in access costs to optimize care.